TUMBUHAN BEGONIA (BEGONIACEAE) DI KECAMATAN ULUIWOI, KABUPATEN KOLAKA - SULAWESI TENGGARA - Harry Wiriadinata; Deden Girmansyah (PTTI, 2011)
Key species for wild Begonia (Begoniaceae) of Uluiwoi village, Kolaka Distric, Southeast Sulawesi presented with simple technical description of each species. B. longifolia has wide distribution, B. aptera and B. flacca endemic of Southeast and Central Sulawesi while B. aptera subsp. hirtissima, B. flacca, B. watuwilensis are endemic of Uluiwoi northern area of mountainous Mekonga.